Farabi’nin dil ve anlam kuramı - Dore, Fatma (My University, 2011)
felsefesi, dilbilim anlambilim (delâlet), zihin/ akıl (nefs/ nutk), tümel (ma'kûlât/ küllî), söz (kavil). ÖZET FÂRÂBÎ’NİN DİL VE ANLAM KURAMI Antikitede Platon ile sorgulanmaya başlayıp akılla sınırlı kalan dil ve anlam ilişkisi, Aristoteles ile nesneler dünyasını da içine alarak realist bir zeminde tartışılmaya başlamıştır. Bin yıldan fazla bir zaman aralığından sonra, X. yüzyılda yaşamış İslam filozofu Ebu Nasr Muhammed el-Fârâbî, Aristoteles’in temelini attığı anlam kuramını sorgulayarak eksik kalan yönleri çözümlemiş ve tamamlamıştır. Bundan hareketle tezimiz Klasik düşüncede bir anlam kuramının aslında ilk kez Fârâbî tarafından kurulduğunu iddia etmektedir. Fârâbî’nin anlamın özerkliğini esas kabul ederek dış dünya, zihin ve dil temelinde geliştirdiği anlam kuramı, filozofun bütün bilimlerin temeli saydığı mantık bilimine bir giriştir. İnsanın doğuştan sahip olduğu yetiler sayesinde anlayabilen ve bunları dilsel olarak ifade edebilen tek canlı türü olduğuna inanan Fârâbî, bu bağlamda “nutk” kavramını inceler. Üç bölüm halinde sunulan çalışmanın girişinde araştırmanın amacı, metot ve kaynakları ile konuyla ilgili yapılmış çalışmalar belirtilmektedir. Fârâbî’nin soruna odaklandığı belli başlı eserlerin tanıtıldığı girişte ayrıca filozofun konu bağlamında kullandığı terminolojiyi Türkçede nasıl karşıladığımız açıklanmaktadır. kaynağı, temel dilsel birimler, sözcük ve sözün parçalarını da kapsayan dil olgusunu incelemektedir. İkinci bölüm delalet olgusuna yoğunlaşmaktadır. Fârâbî’nin anlam kuramına temel olmaları bakımından Yunan ve İslam dünyasında sorunun anlaşılma şekilleri incelenmekte, filozofun bu konuya yaklaşımı ve özgün katkıları belirtilmektedir. Üçüncü bölümde dış dünyanın zihinsel tasarımlar haline geliş süreci ve bunların dilde temsil edilişiyle ilgili Fârâbî’nin açıklamaları sunulmaktadır. nguistics, theory of meaning and language, reference, mind, universals, expression.

Al-FARABI’S THEORY OF LANGUAGE AND MEANING In ancient Greek thought, Plato was the first philosopher to recognize the question of the relationship between language and meaning, but he restricted his investigation of this issue solely to the mind. Later on, his former student Aristotle, through defining entities as being units independent of mind, founded the first realistic theory of meaning. After the space of more than a millennium, Abu Nasr Muhammad Al-Fârâbî, an Islamic philosopher of the 10th century CE, developed his own theory of language and meaning, which expanded and perfected the main principles originally put forward by Aristotle. Therefore, in this study we claim that Al-Fârâbî is, in fact, the true founder of the theory of meaning in classical thought. Al-Fârâbî’s theory of meaning, which is constructed within the triangular relationship of the external world, the mind and language, serves as an introduction to his work on logic, which he sees as being the basis of all possible knowledge. According to Al-Fârâbî human beings are capable of comprehending and expressing everything through their own innate abilities. In this context the concept of “nutq” is an essential one in his theory of meaning for it covers both the act of thinking and the act of utterance. Furthermore, the idea that meanings are autonomous – that is independent of the human mind – is a fundamental one for Al-Fârâbî. This study contains an introduction followed by three sections. The introduction expounds what the aim of this study is, as well as the methods and the sources that are going to be used within it. The introduction also provides a concise list of the studies that have already been done on this subject, and highlights the different approach of this new study to those earlier studies. In the introduction, the works of Al-Fârâbî that specifically deal with the subject matter are introduced. In addition, the basic terminology used by Al-Fârâbî in these works is also elucidated. The first section of the main body of the thesis investigates what Al-Fârâbî’s concept of language is in general. In this context, Al-Fârâbî’s views upon the origin of language, the basic linguistic units, and the role of words as units of sentences are the main topics that have been examined. The second section focuses on the theory of reference in a broad sense. As they form the background to Al-Fârâbî’s meaning theory, the approaches made in this subject within ancient Greek and early Islamic thought are looked at, alongside Al-Fârâbî’s understanding of the issue and his original viewpoints concerning it. The third section shows Al-Fârâbî’s ideas on how the external world, through human perception, is turned into concepts within the human mind, and how these concepts are then represented linguistically. The conclusion, of course, summarizes the findings of the thesis.
Keywords: Anlambilim; Dilbilim; Felsefe